Thermogelling behaviors of aqueous poly(N- isopropylacrylamide-co-2-hydroxyethyl methacrylate) microgel–silica nanoparticle composite dispersions - Hwang, Byung Soo; Kim, Jong Sik; Kim, Ju Min; Shim, Tae Soup (Materials, 2021)
Gelation behaviors of hydrogels have provided an outlook for the development of stimuliresponsive functional materials. Of these materials, the thermogelling behavior of poly(Nisopropylacrylamide) (p(NiPAm))-based microgels exhibits a unique, reverse sol–gel transition by bulk aggregation of microgels at the lower critical solution temperature (LCST). Despite its unique phase transition behaviors, the application of this material has been largely limited to the biomedical field, and the bulk gelation behavior of microgels in the presence of colloidal additives is still open for scrutinization. Here, we provide an in-depth investigation of the unique thermogelling behaviors of p(NiPAm)-based microgels through poly(N-isopropylacrylamide-co-2-hydroxyethyl methacrylate) microgel (p(NiPAm-co-HEMA))–silica nanoparticle composite to expand the application possibilities of the microgel system. Thermogelling behaviors of p(NiPAm-co-HEMA) microgel with different molar ratios of N-isopropylacrylamide (NiPAm) and 2-hydroxyethyl methacrylate (HEMA), their colloidal stability under various microgel concentrations, and the ionic strength of these aqueous solutions were investigated. In addition, sol–gel transition behaviors of various p(NiPAm-co-HEMA) microgel systems were compared by analyzing their rheological properties. Finally, we incorporated silica nanoparticles to the microgel system and investigated the thermogelling behaviors of the microgel–nanoparticle composite system. The composite system exhibited consistent thermogelling behaviors in moderate conditions, which was confirmed by an optical microscope. The composite demonstrated enhanced mechanical strength at gel state, which was confirmed by analyzing rheological properties.
Keywords: 2-hydroxyethyl methacrylate; Composite dispersions; Hydroxyethyl methacrylate; Lower critical solution temperature; N- isopropylacrylamide; N-isopropylacrylamides; Poly (n isopropylacrylamide); Rheological property; Complex colloidal systems; Sol–gel transition behaviors; Stimuli-responsive hydrogels; Thermogelling polymers